Combined laparoscopic abdomino-endoscopic perineal total mesorectal excision for anorectal malignant melanoma: A case report. (2018) - Ohta, Ryo; Inoue, Takahiro; Goto, Manabu; Tachimori, Yuji; Sekikawa, Koji
Highlights: This is the first report of combined laparoscopic abdomino-endoscopic perineal total mesorectal excision for anorectal malignant melanoma. This procedure provides not only better exposure of the extralevator surgical field, but also safety resection margins compared with the conventional abdominoperineal resection. Our experience showed safety and feasible option for anorectal malignant diseases. Abstract: Introduction: This report presents a case of anorectal malignant melanoma treated with combined laparoscopic abdomino-endoscopic perineal total mesorectal excision. Presentation of case: An 82-year-old female presented with hematochezia. Colonoscopy revealed a 5-cm tumor in the anorectal junction, and biopsy specimen showed malignant melanoma. Modified ransanal total mesorectal excision was performed to get the sufficient surgical resection margins. After lymph node dissection in usual manner, mobilizing the rectum to the level of levator ani muscle. Then a skin incision was made around the anus and the transperineal access platform was placed. The fat tissue of the ischioanal fossa was divided until the levator ani muscle was exposed. The oral side of the colon was transected and specimen was extracted through the perineal incision site. Then stoma was placed laparoscopically. Discussion: This procedure provides not only better exposure of the extralevator surgical field, but also efficient resection margins compared with the conventional andominoperineal resection. Conclusion: To the best of our knowledge, this is the first report of combined laparoscopic abdomino-endoscopic perineal total mesorectal excision for anorectal malignant melanoma. Our experience showed safety and feasible option for anorectal malignant diseases.